Implementation of ATEX standards in the context of mining activity in Colombia (2017)
Mining in Colombia is regulated by the Mining Safety Code, and although it had not been updated since 1987, the references on safety that the code has owned were based on international standards. However, these references do not have a mandatory adoption, and despite a strong component on occupational safety and health, Decree 1886/15 continues to show a rough technical content that could consent the extension of mining disasters associated with explosions in Colombia. This article specifies the international mine safety regulations, and critically analyzes the absence of its applicability in the country. Although the national outlook is discouraging because of the lack of rigor from governmental entities in enforcement, mining in other countries has improved in safety as a result of implementing standards that ensure quality operations and procedures, machinery, and human resources, decreasing mining disasters.